2017
DOI: 10.4172/interventional-cardiology.1000591
|View full text |Cite
|
Sign up to set email alerts
|

Vaso-vagal reflex in paediatric patients with cardiac catheterization: Integrative literature review

Abstract: Vaso-vagal reflex is a significant and common complication in paediatric patients with cardiac catheterization. Vaso-vagal reflex includes several symptoms, such as tachycardia, pressure, light headedness, nausea, or cyanosis that are severe threats to cause death. To understand the vaso-vagal reflex among paediatric patients with cardiac catheterization, we conducted integrative literature to review content about nursing with the reflex. We reviewed, analysed, and synthesized published research and grey liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In order to understand the vaso-vagal reflex among pediatric patients with cardiac catheterization, Kraisornsawat et al [6], conducted a literature review with special focus on caring for such patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to understand the vaso-vagal reflex among pediatric patients with cardiac catheterization, Kraisornsawat et al [6], conducted a literature review with special focus on caring for such patients.…”
Section: Introductionmentioning
confidence: 99%
“…Carini et al [5], described a case of an aorto-pulmonary window identified during a surgery for Type A interrupted aortic arch, which was repaired without any hindrance. Kraisornsawat et al [6], conducted a literature review with special focus on caring for pediatric patients with cardiac catheterization suffering from vaso-vagal reflex. Nunokawa [7] authored a review on the creation of a native arteriovenous fistula (AVF) for the purpose of hemodialysis (HD), and the factors to be considered while proceeding for the same…”
Section: Introductionmentioning
confidence: 99%